Motivasi Kerja dan Efikasi Diri terhadap Kinerja Guru Penggerak Melalui Resiliensi di Kabupaten Kutai Timur - Kusumaningrum, Tri Agustin; Azainil, Azainil; Warman, Warman (LP. Ma'arif Janggan Magetan, 2024)
The aim of this research is to explain: 1) The influence of work motivation on the performance of East Kutai Regency driving teachers, 2) The influence of self-efficacy on the performance of East Kutai Regency driving teachers, 3) The influence of resilience on the performance of East Kutai Regency driving teachers, 4) The influence of work motivation on the resilience of driving teachers in East Kutai Regency, 5) The influence of self-efficacy on the resilience of driving teachers in East Kutai Regency, 6) The indirect influence of work motivation on performance through the resilience of driving teachers in East Kutai Regency, and 7) The indirect influence of self-efficacy on the performance of driving teachers through resilience in East Kutai Regency. Type of quantitative research. The research population was school principals and driving teachers for Classes 5, 7 and 8 in East Kutai Regency. The sampling method used proportional sampling of 20 school principals and 51 teachers. Results Based on the results of the research and discussion, it can be concluded as follows: 1) Work motivation has a direct positive effect on the performance of teachers in East Kutai Regency. 2) Self-efficacy has a direct positive effect on the performance of East Kutai Regency driving teachers. 3) Teacher resilience has a direct positive effect on the performance of teachers in East Kutai Regency. 4) Work motivation has a direct positive effect on the resilience of teachers driving East Kutai Regency. 5) Self-efficacy has a direct positive effect on the resilience of teachers driving East Kutai Regency. 6) There is a significant influence between work motivation and performance through the resilience of driving teachers in East Kutai Regency. 7) There is a significant influence between self-efficacy on the performance of driving teachers through resilience in East Kutai Regency.